Four-Tier Diagnostic Test With Certainty of Response Index on The Concepts of Fluid. (February 2019) - Diani, R; Alfin, J; Anggraeni, Y M; Mustari, M; Fujiani, D
Abstract: The four-tier diagnostic test with certainty of response index (CRI) is an instrument that can be used to identify student misconceptions. This instrument is the result of development of a three-tier multiple-choice diagnostic test equipped accompanied by the students' confidence level. This instrument which is intended for fluid concepts learning material was developed through the following stages: analysis, design, development, implementation and evaluation (ADDIE). The results of expert validation indicate that the developed instrument is valid. Furthermore, the instrument was tried-out to the twelfth grade students of class Science 1 of Senior High School 1 Pagelaran to determine the validity, reliability, level of difficulty, and the differentiating power of each question. There are twenty items out of twenty-five items that were feasible to be used in identifying the students' misconceptions.